Transfer of elements relevant to radioactive waste into chironomids and fish in boreal freshwater bodies - Majlesi Soroush; Akkanen Jarkko; Roivainen Päivi; Tuovinen Tiina S.; Sorvari Jouni.; Naarala Jonne; Juutilainen Jukka (Elsevier B.V., 2022)
Information on transfer of elements and their radionuclides is essential for radioecological modeling. In the present study, we investigated the transfer of Cl, Co, Mo, Ni, Se, Sr, U and Zn in a boreal freshwater food chain. These elements were selected on the basis that they have important radionuclides that might be released into the biosphere from various stages of the nuclear fuel cycle. Water, sediment, chironomid larvae (Chironomus sp.), roach (Rutilus rutilus) and perch (Perca fluviatilis) were sampled from two ponds near a former uranium mine and one reference pond located further away from the mining area. Concentrations measured in water, sediment and the three animal species indicated the importance of sediment as a source of uptake for most of the elements (but not Cl). This should be considered in radioecological models, which conventionally predict concentration in aquatic organisms from concentration in water. The results also show that the assumption of linear transfer (constant concentration ratio) may not be valid for elements into fish. The results of this study show that further basic research is needed to understand the fundamental processes involved in transfer of elements into freshwater organisms in order to develop radioecological models.